KONSEP ‘MALUM IN SE’ DAN ‘MALUM PROHIBITUM’ DALAM FILOSOFI PEMBERANTASAN KORUPSI - Shidarta Shidarta (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Constitutional Court decision No. 003/PUU-IV/2006 has construed the connotation of Article 2 paragraph (1) of Law No. 31 Year 1999 by shifting the concept of ‘malum in se’ to that of ‘malum prohibitum’ in term of the element of ‘unlawfulness’ in that article. Is such an interpretation relevant enough amid the current corruption battle in this country? This article discusses this question by using the perspective of legal philosophy. The author of this article concludes that in the meantime, truth and justice values as constantly underlined by legal philosophy should be upheld as the strategy to strengthen the collectivity rather than the individuality principles in the Indonesian legal system. In this point of view, the shifting of the ‘malum in se’ to ‘malum prohibitum’ concepts can affect the principle of authority in the effort of corruption erradication in Indonesia. Keywords: malum in se, malum prohibitum, corruption. Abstrak Putusan MK Nomor 003/PUU-IV/2006 memberi penafsiran yang mengubah konsep ‘malum in se’ menjadi ‘malum prohibitum’ terhadap makna melawan hukum dalam Pasal 2 ayat (1) Undang-Undang Nomor 31 Tahun 1999. Persoalannya adalah: apakah pergeseran makna ini dapat dianggap tepat? Tulisan ini menjawab pertanyaan tersebut dengan menggunakan perspektif filsafat hukum. Dalam kondisi kekinian iklim pemberantasan korupsi di Indonesia, asas kebenaran dan keadilan yang digarisbawahi oleh filsafat hukum itu harus dibaca sebagai sebuah strategi untuk lebih memperkuat asas persekutuan (kolektivitas) dalam sistem hukum dibandingkan dengan asas kepribadian. Dalam konteks ini, maka pergeseran konsep ‘malum in se’ ke ‘malum prohibitum’ dapat dipandang sebagai pelemahan asas kewibawaan hukum dalam upaya pemberantasan korupsi di Indonesia. Kata kunci: malum in se, malum prohibitum, tindak pidana korupsi.